Temperature Calibration of a Differential Pair based Direct Digital Synthesizer through Subsampling Spectral Analysis - Lämmle, Benjamin; Wagner, Christoph; Jäger, Herbert; Weigel, Robert (Topical Meeting on Silicon Monolithic Integrated Systems in RF Systems, 2010)
The temperature behavior of a high speed direct digital synthesizer with a maximum clock frequency of 16.8 GHz and a power consumption of 488 mW at room temperature is investigated. The DDS has been manufactured in a 200-GHz ft SiGe bipolar technology and occupies a chip area of 1.15 mm2. A subsampling approach is introduced to analyze the output spectrum of the DDS. A calibration is performed over temperature to improve the spectral performance of the DDS. The calibration is based on a two point measurement and the use of a look-up table. After calibration, the third harmonic is below 53 dBc and a narrow band SFDR is nearly constant at 38 dBc.
elib2cris::1512001600,laemmle2010